Kinanthropometry X : proceedings of the 10th International Society for Advancement of Kinanthropometry Conference, held in conjunction with the 13th Commonwealth International Sport Conference - International Society for Advancement of Kinanthropometry. International Conference (10th : 2006 : Melbourne, Australia); Marfell-Jones, Mike; Olds, Tim; Commonwealth International Sport Conference (13th : 2006 : Melbourne, Australia) (New York, NY : Routledge, 2008)
42